Evart van Dieren een kroniek van het falen - Bos, Jaap (Amsterdam University Press, 2008)
This remarkablpe title describes the life of one of Holland's most remarkable figures: medical practitioner Van Dieren (1861-1940), Amsterdammer and prolific writer who caused quite a stir in his days. The author recounts the life and times of Van Dieren in the form of a series of narratives about the fights of this Dutch Don Quixote with his particular windmills. Individual chapters deal with his life, work, personal style, friendships and enmities, his discussions with psychoanalysts, socialists, scientists and above all of his tragic-comical failures. Unique source material is used to reconstruct this picture, such as the correspondence between Van Dieren and a large number of well-known Dutchmen, including novelist Van Eeden, Nobel laureate C.Eijkman, the philosopher Bolland, politician De Savornin Lohman, Queen Emma, and many others. Marginality and non-conformity are the key themes that run through the life of this observer which made him one of the most successful failures in Dutch history.